Growing usage of internet banking : a study on the effects of internal attributes on the frequency of internet banking usage among undergraduates in Singapore. - Lim, Yi Ling. (2013)
The proliferation of banking platforms due to technological advancement has brought not only more options, but also greater convenience to banking customers. In recent years, the usage of Internet banking has grown substantially and many banks are tapping on this trend to offer Internet banking facilities to cater to customers more efficiently. The question is therefore how banks can market their Internet banking facilities to their customers effectively, such that customers will be willing to adopt the new banking platform. This is what we have in mind as we set out to conduct our study. This study seeks to investigate the internal attributes that influence the frequency of Internet banking usage among undergraduates in Singapore. We aim to determine the impact of undergraduates’ security consciousness, maximiser characteristics and their desire for instant gratification on their usage of Internet banking. We further aim to establish how the relationship between each of these three internal attributes and the frequency of Internet banking usage is moderated by gender.